2013
DOI: 10.1007/s10995-013-1290-1
|View full text |Cite
|
Sign up to set email alerts
|

Literacy, Pregnancy and Potential Oral Health Changes: The Internet and Readability Levels

Abstract: The purpose of this study is to evaluate the readability level and content of articles concerning pregnancy and the periodontium which are presented on internet websites. Websites were selected from Google, Yahoo, and Bing. The sites which were excluded were: commercial sites; blogs; dental office sites; sites with articles having fewer than 20 sentences; duplicated search results; and non-secure sites (N = 137). The grade level was determined from the SMOG reading index. Content was scored for specific pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…[3] have investigated methods for estimating user proficiency and readability of results, as well as for re-ranking results according to this information. In health web search, accounting for the readability of the retrieved information is a core requirement to effectively support users (see for example [16]). Health consumers may have a limited understanding of the medical terminology and processes, and thus they should be shown text that is simple to understand and limits expert terminology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] have investigated methods for estimating user proficiency and readability of results, as well as for re-ranking results according to this information. In health web search, accounting for the readability of the retrieved information is a core requirement to effectively support users (see for example [16]). Health consumers may have a limited understanding of the medical terminology and processes, and thus they should be shown text that is simple to understand and limits expert terminology.…”
Section: Introductionmentioning
confidence: 99%
“…While recent research has proposed sophisticated readability estimation methods [3,7], often tailored to specific domains [17], traditional readability measures such as the Automated Readability Index and the Gunning Fog Index are extensively used for assessing information on the web (see for example [16,18]). These long-established readability measures consider the surface level of the text contained in web pages, that is, the wording and the syntax of sentences.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng and Yu have reported on the readability of electronic health records compared to Wikipedia pages related to diabetes and found that readability measures often do not align with user ratings of readability [22]. A common finding of these studies is that, in general, health content available on Web pages is often hard to understand by the general public; this includes content that is retrieved in topranked positions by current commercial search engines [4,5,6,7,8,9].…”
Section: Related Workmentioning
confidence: 99%
“…These measures generally rely on surface-level characteristics of text, such as characters, syllables and word counts (missing citation). While these measures have been widely used in studies investigating the understandability of health content retrieved by search engines (e.g., [4,5,6,7,8,9,18,21]), our preliminary work found that these measures are heavily affected by the methods used to extract text from the HTML source [13]. We were able to identify specific settings of an HTML preprocessing pipeline that provided consistent estimates, but due to the lack of human assessments, we were not able to investigate how well each HTML preprocessing pipeline correlated with human assessments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation